THE EFFECT OF ROAD INFRASTRUCTURE, ELECTRICITY AND WATER ON THE GROWTH OF GROSS REGIONAL DOMESTIC PRODUCTS IN GOWA DISTRICT, SOUTH SULAWESI PROVINCE - Ms, Yanti; Naidah, Naidah; Badollahi, Ismail (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
This study aims to: (1) Know the road infrastructure has a positive and significant effect on GDP growth in Gowa Regency, South Sulawesi Province (2) Knowing the electricity infrastructure has a positive and significant effect on GDP growth in Gowa Regency, South Sulawesi Province positive and significant impact on GRDP growth in Gowa Regency, South Sulawesi Province (4) Knowing which factors predominantly affect GDP in Gowa Regency, South Sulawesi Province. Data processing techniques using multiple linear regression through SPSS version 16. This research uses quantitative research methods and is processed with the needs of the model used. The results showed that simultaneously the road, electricity and water variables had a positive and significant effect on GDP growth in Gowa Regency, South Sulawesi Province. Partially roads, electricity and water have a positive and significant effect on GDP growth in Gowa Regency, South Sulawesi Province.